Memperkuat Persatuan Bangsa di Era Globalisasi Mahasiswa Prodi Teknik Elektro Universitas PGRI Adi Buana Surabaya: Indonesia - Haris Tio Priananda; Ayunda Frischa Nadira; Dwi Helena Yuliastari; Tedo Hanu; Rachmad Rangga Wijaya; Putri Rahayu Sejati; Nabila Natcjwa Amanda; Fitri Novita; Adhe Riana; Aldo Ridho; Elvira Mamun; Putri Mariana; Nurul Fitrianingtyas; Suyono Suyono (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2024)
The era of globalization brings big challenges to the unity of the Indonesian nation, including among students. This research focuses on the role of Electrical Engineering Study Program students at PGRI Adi Buana University, Surabaya in strengthening national unity amidst globalization. The method used is a case study with a qualitative approach, involving in-depth interviews and participatory observation of 5 Electrical Engineering students. The research results show that students can contribute through: 1) Understanding and interpreting the concept of national unity, 2) Applying the principles of unity in their daily activities, 3) Working together with students from other majors to strengthen national unity, 4) Contributing to maintaining national values in the era of globalization, 5) Using social media responsibly.